SCIENTIFIC AND EDUCATIONAL GEOPORTAL AS INSTRUMENT OF INTEGRATION OF RESULTS OF SCIENTIFIC RESEARCHES OF THE REPUBLIC OF BASHKORTOSTAN BY THE LARGE NUMBER OF USERS - Olga I. Hristodulo (Открытое образование (Москва))
The article covers the urgency of establishing a scientifi c and educational geoportal as a single data center for the Republic of Bashkortostan, providing quick access to a distributed network of geospatial data and geoservices to all responsible and interested parties. We considered the main tasks, functions and architecture of a scientifi c and educational geoportal for different types of users. We also carried out a comparative analysis of the basic technology for the development of mapping services and information systems, representing the major structural elements of geoportals. As an example, we considered information retrieval problems of the scientifi c and educational geoportal for the Republic of Bashkortostan.